Does the Rotator Cuff Tear Pattern Influence Clinical Outcomes After Surgical Repair?. Issue 3 (26th March 2018) - Watson, Scott; Allen, Benjamin; Robbins, Chris; Bedi, Asheesh; Gagnier, Joel J.; Miller, Bruce
Background: Limited literature exists regarding the influence of rotator cuff tear morphology on patient outcomes. Purpose: To determine the effect of rotator cuff tear pattern (crescent, U-shape, L-shape) on patient-reported outcomes after rotator cuff repair. Study Design: Cohort study; Level of evidence, 3. Methods: Patients undergoing arthroscopic repair of known full-thickness rotator cuff tears were observed prospectively at regular intervals from baseline to 1 year. The tear pattern was classified at the time of surgery as crescent, U-shaped, or L-shaped. Primary outcome measures were the Western Ontario Rotator Cuff Index (WORC), the American Shoulder and Elbow Surgeons (ASES), and a visual analog scale (VAS) for pain. The tear pattern was evaluated as the primary predictor while controlling for variables known to affect rotator cuff outcomes. Mixed-methods regression and analysis of variance (ANOVA) were used to examine the effects of tear morphology on patient-reported outcomes after surgical repair from baseline to 1 year. Results: A total of 82 patients were included in the study (53 male, 29 female; mean age, 58 years [range, 41-75 years]). A crescent shape was the most common tear pattern (54%), followed by U-shaped (25%) and L-shaped tears (21%). There were no significant differences in outcome scores between the 3 groups at baseline. All 3 groups showed statistically significant improvement from baseline to 1 year, but analysis failed to show any predictive effect in the change in outcome scores from baseline to 1 year for the WORC, ASES, or VAS when tear pattern was the primary predictor. Further ANOVA also failed to show any significant difference in the change in outcome scores from baseline to 1 year for the WORC ( P = .96), ASES ( P = .71), or VAS ( P = .86). Conclusion: Rotator cuff tear pattern is not a predictor of functional outcomes after arthroscopic rotator cuff repair.